Cateterismo percutáneo en el niño: estudio de 44 pacientes. - Rivas Sierra, J. Alfredo; Alonso Moreno, Yolanda; Pérez, Lázara; Acosta, Cayetano; Jiménez, Luis (Revista Cubana de Pediatría, 2023)
Se presenta la experiencia obtenida en 44 pacientes.